Pulmonary embolism management in the emergency department: part 2. Issue 1 (5th April 2022) - Serebriakoff, Philippa; Cafferkey, John; de Wit, Kerstin; Horner, Daniel E; Reed, Matthew J
Abstract : Pulmonary embolism (PE) can present with a range of severity. Prognostic risk stratification is important for efficacious and safe management. This second of two review articles discusses the management of high-, intermediate- and low-risk PE. We discuss strategies to identify patients suitable for urgent outpatient care in addition to identification of patients who would benefit from thrombolysis. We discuss specific subgroups of patients where optimal treatment differs from the usual approach and identify emerging management paradigms exploring new therapies and subgroups.